STRATEGI KEBIJAKAN FISKAL PEMERINTAH DALAM MENINGKATKAN PEREKONOMIAN INDONESIA PADA MASA PANDEMI COVID-19 - Kurnia Putri Mirani; Aniela Nania Margareth; Nila Cahyarani; Agus Maulana (Bilancia : Jurnal Ilmiah Akuntansi, 2021)
The Covid-19 pandemic has many impact in all areas of life, especially the economy. Various strategies have been carried out by the government to improve economic conditions facing recession, one of the strategies is fiscal policy. Fiscal policy is the government's authority to adjust the state revenue and expenditure budget with the predetermined state budget. This study aims to determine the various policies undertaken by the government to improve the Indonesian economy during the Covid-19 pandemic. Descriptive qualitative method is applied in this research with literature study data collection techniques. The results of this study indicate several fiscal policies implemented by the government in improving the Indonesian economy during the pandemic, including refocusing the 2020 State Budget as an efficient measure of state spending and tax incentive programs to relieve taxpayers. From these policies, fraud is still found, so the government needs to re-evaluate it. The results of this study are expected to be a source of the latest information for those in need in the future. Pandemi Covid-19 berdampak pada semua bidang kehidupan, khususnya bidang ekonomi. Berbagai strategi dilakukan pemerintah untuk meningkatkan kondisi perekonomian yang mengalami resesi, salah satunya dengan kebijakan fiskal. Kebijakan fiskal merupakan wewenang pemerintah untuk menyesuaikan anggaran pendapatan dan pengeluaran negara dengan APBN yang sudah ditentukan sebelumnya. Penelitian ini bertujuan untuk mengetahui berbagai kebijakan yang dilakukan pemerintah untuk meningkatkan perekonomian Indonesia pada masa pandemi Covid-19. Metode kualitatif deskriptif diterapkan dalam penelitian ini dengan teknik pengumpulan data studi pustaka. Hasil dari penelitian ini menunjukkan beberapa kebijakan fiskal yang diterapkan pemerintah dalam meningkatkan perekonomian Indonesia pada masa pandemi, di antaranya refocusing APBN 2020 sebagai tindakan efisiensi pengeluaran negara serta program insentif pajak untuk meringankan wajib pajak. Dari kebijakan-kebijakan tersebut, masih ditemukan kecurangan sehingga pemerintah perlu melakukan evaluasi kembali. Hasil penelitian ini diharapkan dapat menjadi sumber informasi terbaru bagi pihak yang membutuhkan pada waktu mendatang.